Highly Conductive and Mechanically Robust NiFe Alloy Aerogels: An Exceptionally Active and Durable Water Oxidation Catalyst. Issue 37 (18th August 2022) - Liang, Caiwu; Pan, Weisheng; Zou, Peichao; Liu, Peng; Liu, Kangwei; Zhao, Guangyao; Fan, Hong Jin; Yang, Cheng
Abstract: Poor stability of nanostructured electrocatalysts at rigorous industrial conditions significantly inhibits their performances in practical electrolyzers. Although many substrate‐supported nanostructured electrocatalysts present attractive performance at small currents, they cannot sustain industry‐level high current densities for long‐term operation. Herein, by chemically organizing nanoscale electrocatalysts into a macroscopic substrate‐free metallic alloy aerogel, this NiFe‐based nano‐catalyst achieves 1000‐h durability at industrial‐level current densities, with exceptionally high activities of 500 mA at the overpotential of only 281 mV. This NiFe alloy aerogel is constructed by a magnetic‐field assisted growth and assembly of ferromagnetic NiFe nanoparticles, in which nanowires are loosely crosslinked by metallic joints. This alloy aerogel shows a high electric conductivity of 500 S m −1, structural stability for more than 1.5 years in alkaline electrolyte, and almost complete recovery after compression exceeding 50% strain for 1000 cycles. The excellent mechanical stability of this metallic aerogel behaves as the key contributor to the superior electrocatalytic stability under industrially relevant conditions. This work offers a paradigm for electrode design for the practical application of nano‐catalysts in industrial alkaline water electrolysis. Abstract : The poor trade‐off between catalytic activity and structural stability of nano‐catalysts under rigorous industrial conditions has been a long‐lasting challenge for industrial‐level application. A highly compressible and mechanically robust alloy aerogel is fabricated as a highly catalytic active and durable oxygen evolution reaction catalyst at high current densities.